Avaliação formativa na concepção docente : a negação da avaliação classificatória e a reprodução da lógica capitalista - Alixandre, Maria Aparecida Rosa de Andrade (2024)
The present study deals with Formative Assessment, which has influenced the conception, practices, policies and training processes in Basic Education, although learning assessment is a phenomenon full of contradictions and denials. The thesis defended is that Formative Assessment, guided by capitalist logic, denies the discourse of denial of Classification Assessment. To respond to problems arising from social practice, we define, as an epistemological path, Historical and Dialectical Materialism, which makes it possible to grasp the essence of the phenomenon investigated in its real and effective existence, that is, in its concreteness, analyzing its contradictions in social practice and in its relationship with other phenomena. To analyze how assessment materializes in the teaching conception, we carried out an analysis based on two approaches: the macrostructural, with regard to the historicity of assessment and its relationship with the social structure, and the microstructural, with regard to the conception of teachers on Formative Assessment. The empirical research was carried out in three schools in the city of João Pessoa, Paraíba, with six teachers from the 5th year of Elementary School. The interviews carried out highlight the denial and contradictions of Classification Assessment and the prominence of Formative Assessment in the teaching conception. However, this rejection of Classification Assessment does not imply its absence in teachers' pedagogical practice. The research makes it possible to point out that both Classificatory Assessment (Traditional Pedagogy) and Formative Assessment (New Pedagogy), although developed at different historical moments, are aimed at strengthening and maintaining the capitalist system. Thus, if education is at the service of the bourgeoisie, it continues to reproduce the principles of this social structure. To this end, Formative Assessment presents itself as an element of transformative education, but it is not a revolutionary change, based on the formation of critical subjects, capable of transforming society. But, yes, changes, albeit contradictory, aimed at maintaining the bourgeois class and the capitalist system. Finally, the work presents the Dynamic Assessment proposed by Historical-Critical Pedagogy as an alternative to Classificatory Assessment and Formative Assessment, since this Pedagogy denies and incorporates elements of Classificatory Assessment and Formative Assessment.